An extended π-backbone for highly efficient near-infrared thermally activated delayed fluorescence with enhanced horizontal molecular orientation. Issue 2 (13th December 2021) - He, Jian-Li; Tang, Yukun; Zhang, Kai; Zhao, Yue; Lin, Yu-Ching; Hsu, Chih-Kai; Chen, Chia-Hsun; Chiu, Tien-Lung; Lee, Jiun-Haw; Wang, Chuan-Kui; Wu, Chung-Chih; Fan, Jian
Abstract : A novel D–A1–A2–A3 configuration has been developed for achieving NIR-TADF with EQE of 21.9% at 712 nm. Abstract : Near-infrared thermally activated delayed fluorescence (NIR-TADF) materials with emission over 700 nm have been insufficiently investigated mainly due to the limited choice of strong donor/acceptor units for molecular construction and the limited electronic coupling between the donors and acceptors. Herein, a novel D–A1–A2–A3 configuration was developed for the design of a NIR-TADF material (TPA-CN-N4-2PY), in which three types of sub-acceptor units (CN: cyano; N4: dipyrido[3, 2- a :2′, 3′- c ]phenazine; PY: pyridine) were incorporated into a molecular skeleton to reinforce the electron-accepting strength. The attachment of two pyridine units on TPA-CN-N4 produced TPA-CN-N4-2PY with an extended π-backbone, which shifted the electroluminescence (EL) emission into the NIR region and enhanced the horizontal ratio of emitting dipole orientation ( Θ // ) simultaneously. TPA-CN-N4-2PY-based OLEDs demonstrated a record-high external quantum efficiency (EQE) of 21.9% with an emission peak at 712 nm and Θ // = 85% at the doping ratio of 9.0 wt%. On the contrary, the parent compound TPA-CN-N4-based OLEDs at the same doping ratio achieved an EQE of 23.4% at 678 nm with Θ // = 75%. This multiple sub-acceptors approach could enrich the design strategy of the NIR-TADF materials, and the large conjugated system could improve the Θ // for achieving efficient emitters.